Study of environmental performance of the boiler ТПП-210A at different dust feeding systems - Юрасова, Оксана Георгіївна (Technology audit and production reserves, 2014)
The environmental problems of reduce the harmful effects of thermal environment are actual for Ukraine. Replacing of old equipment requires substantial new funds. Therefore, an important task in the energy of Ukraine is extending the life of existing thermal power plants. The effectiveness of the fuel regime of energy boilers equipped with a high concentrated dust feeding with pressure on burners at combustion of low-reactive worsen quality coal is investigated in the article. The results of the comparative tests of TPP-210A boilers with dust feeding with a high concentration and traditional dust feeding system are given. The comparative experiments, experiments to determine the effect of operational factors on the value of emissions of nitrogen oxides are included in the extent of testing. Analysis of comparative research shows that environmental (for NOx) performance of the boiler equipped with dust feeding system differ from the boilers with traditional pulverization system and reducing of NOx emissions is observed. The experience of using the system of high concentration dust feeding (HCDF) on boilers of Trypilska TPP can recommend it for implementation in similar boilers of Ukrainian power stations. Based on experimental studies performed on the boiler TPP-210A with the traditional dust feeding system and dust feeding system of high concentration it is found that the dust feeding system of high concentration has advantages over the traditional system, namely reduction of NOx emissions, the cost of electricity for own needs and repair work.